Apocrine Adenocarcinoma in the Eyelid of a Miniature Pinscher - Stern, Adam W.; Eisele, Lauren P. (Brazilian Journal of Veterinary Pathology, 2011)
A 12-year-old spayed female miniature pinscher canid presented to the referring veterinarian with a 1 month history of a right eyelid mass. No other masses besides a previously diagnosed lipoma were identified after physical examination and thoracic radiographic examination. Histologically, neoplastic cells formed glands and were subdivided by a fibrous stroma, exhibited moderate cellular pleomorphism, and were immunoreactive for cytokeratin 7. Based on these findings an apocrine adenocarcinoma of the eyelid was diagnosed.